Ethnocultural markers of digital political discourse in social networks (based on the speeches and publications of the presidents of Uzbekistan, Russia, and the United States) - Toshboeva, Munisa Rustamovna (The Lingua Spectrum, 2026)
This article undertakes a comparative study of ethno-cultural markers found in the digital public communications of the heads of state of Uzbekistan, Russia, and the United States on social media platforms. The material comprises open posts, video addresses, and official statements by Shavkat Mirziyoyev, Vladimir Putin, and Donald Trump. A key stage of the research involves defining the concept of “digital political discourse.” The classical tradition treats political discourse as institutionally conditioned speech activity through which those in power legitimize their decisions, construct a “self – other” dichotomy, and orchestrate mass political action. The author reconstructs the rhetorical devices employed by political leaders in the online environment, traces their embeddedness within national axiological systems, and describes the mechanisms of audience influence. The comparative analysis provides grounds to identify three types of cultural models: collectivist-traditionalist (Uzbekistan), state-centric with a historical-mobilizational vector (Russia), and individualistic-personalist (USA). The analysis reveals universal features of digital political discourse – impact orientation, strategic design, emotionalization, identity construction, and mediatization – each of which acquires specific ethno-cultural content. The paper concludes by substantiating the thesis that the digital environment does not smooth out cross-cultural differences but, on the contrary, renders them more pronounced.